The Scale and Selectivity of Foreign-Born PhD Recipients in the US - Grogger, Jeffrey; Hanson, Gordon (American Economic Review, 2013)
We study the scale and selectivity of foreign-born PhD students in science and engineering. We focus on students from China, India, Korea, and Taiwan, which together account for most roughly one-third of science and engineering PhD students in the United States. The selectivity of these students is high, as measured by their fathers' relative education levels. In China and India, fathers of students who receive US PhDs in these fields are roughly 15 times more likely to have a BA degree than their contemporaries are to have tertiary education. Over time, selectivity falls for China but the trend for other countries is ambiguous.